Manuscript Writing Workshop for Authors – 2018 - Pokhrel, Rishi; Bajracharya, Barhsa (Medical Journal of Shree Birendra Hospital, 2018)
The workshop covered various aspects of medical research, writing and publishing including planning a research project, statistics, referencing, literature search, the art of writing, formatting of scientific manuscripts, submission, peer review and editorial process and ethical issues in medical research including plagiarism. The workshop included hands on practice on submission process of a manuscript in an actual journal.